Java picture archiving and communication system - Carrillo, Thryza Michelle M. (2001)
This paper is a technical documentation of the Java Picture Archiving and Communication System. This thesis is a replication of the existing PACS system, however, this version is an open source application, which is completely free of charge. The first part of the paper, the introduction, presents to the reader the details of the problem that the developers are working on. It briefly identifies the nature of the problem, its extent and the team's analysis of the issues concerning this. It also discusses the proposed solution to the problem and the present solution that the authors have formulated. A review of related literature summarizes articles written about the topic and relates our comments about the said papers. The discussion section of the paper provides the details of how the team has come up with the soultion and the changes made along the way. It emphasizes on the major components of the application such as the Graphical User Interface, the Database and the Communications System. It also points out major issues regarding the development of the application such as the operating system and the language to be used. It chronologically explains the decisions made by the team members, as well as the factors considered during decision-making. In the discussion of the Graphical User Interface, we describe the features of the application with regards to the imaging tools and their functionality. The details of the design and the software used in its implementation are also mentioned in this portion. The changes made in the design and the reason for these modifications is also briefly explained. The discussion on the database expounds the design of the schema to be used. It also presents the tables that will determine the possible queries on the database. A significant portion of the discussion is devoted to the selection of the best Database software to be utilized. Here we also justify the choices made by weighing the advantages against the disadvantages of each software candidate. The communications portion of the discussion gives the steps undertaken by the team in order to implement the chat function. The conclusion and recommendations part gives an over-all review of the project as seen at the developers' view. It also gauges the performance of the team in terms of speed and efficiency. Finally, it gives suggestions for those who will be interested to continue or develop the project.